A Nanotechnological Exploration of Touch - Thomas, Paul (The MIT Press, 2009)
The Midas project investigates the trans-mediational space between skin and gold. Research for the project was conducted through the analysis of data recorded with an Atomic Force Microscope (AFM). The AFM, in its force spectroscopy mode, gathers data by picking up the surface vibrations as the cantilever touches the cell. The Midas project culminated in an installation that included data projection and audio work utilizing subsonic speakers to make the data from the atomic vibrations audible and palpable.